PENGEMBANGAN MEDIA PEMBELAJARAN FLASH CARD PADA PAPAN BERGAMBAR MATERI SISTEM PERNAPASAN MANUSIA UNTUK SISWA KELAS V SDN Pagung 2 - Lina Duwiana; Farida nurlaila Zunaidah; Tutut Indah Sulistiyowati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem in Natural and Social Science (IPAS) learning at the elementary school level remains centered on students' low comprehension due to the use of less engaging instructional media. Observations and interviews conducted in Class V at SDN Pagung 2 revealed that the teacher still relied on limited media, such as A4 paper-based teaching aids, lengthy educational videos, and less attractive images. As a result, most students failed to achieve the minimum mastery criteria (KKM) for the human respiratory system topic. This study aims to develop an instructional media in the form of flash cards mounted on a picture board to improve students’ understanding of the material. The research employed a Research and Development (R&D) method using the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. Data collection techniques included observation, interviews, expert validation questionnaires, teacher and student practicality questionnaires, and learning outcome tests. The validation results indicated the media was highly valid, with a score of 93%. Teacher practicality responses reached 96%, and students found the media highly attractive and easy to use. The effectiveness test, measured through pretest and posttest, showed an increase in the average score from 65 to 87, with classical completeness reaching 85%. The flash card media on a picture board proved to be valid, practical, and effective in teaching the human respiratory system in IPAS for fifth-grade students. In addition to improving learning outcomes, the media also fostered students’ interest and active participation.